Anatomical Variations of the Urethera and their Role in Persistent Inflammatory Uropathies - Muhammad Akhtar, Huma Jawad, Muhammad Farhan Qureshi, Imran Hussain, Sabeeh Ubaid Ullah, Kanwal Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To investigate the prevalence and clinical significance of anatomical variations of the urethra in patients with persistent inflammatory uropathies (PIUs) across a multicenter cohort. Materials And Methods: This multicenter study was observational and prospective conducted between January to December 2022. The total number of participants was 1,218 adult patients (≥18 years), presenting with LUTS that were recurrent or persistent, as well as an inflammatory uropathy that had been confirmed through various diagnostic modalities, such as cystoscopy, urine cytology and histopathology. All enrolled subjects had undergone high-res pelvic MRI, retrograde urethrogram, voiding cystourethrogram and urodynamic evaluation. Documented anomalies consisted of anatomical variations in the urethra (such as duplicate, meatal stenosis, diverticula, posterior urethral valves in males and ectopic urethral orifice). In addition, logistic regression analyses adjusted for age, sex, comorbidities, and prior history of instrumentation, were utilized to determine whether the persistence of PIU was associated with the anatomical variations found. Results: 382 patients (31.4%) out of 1,218 who had anatomical differences. The anatomical variations include meatal stenosis (12.6%), urethral diverticula (9.8%), and ectopic orifices (6.3%). The rates of recurrent UTIs (OR = 2.41, 95% CI: 1.89-3.08, p < 0.001), chronic urethritis (OR = 3.02, 95% CI: 2.31-3.95, p < 0.001), and treatment failure (OR = 2.78, 95% CI: 2.15-3.60, p < 0.001) were significantly greater in patients with anatomical variations than for those without. A total of five statistically significant associations (p < 0.05) have been verified in the multivariate analysis. Conclusion: Variant anatomy of the Urethra is common in persistent inflammatory uropathies and associated with treatment failures and symptom recurrence. Therefore, in the Diagnosis of PIU, Imaging and Assessment of the urethra should be considered Routine in the Diagnostic Algorithm. Keywords: Urethral anomalies; inflammatory uropathy; persistent urinary tract infection; urethral stenosis; urethral duplication; multicenter study; uroimaging.